Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Di BEI Periode 2016-2018 - Cindy Dezer Wijaya, Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study was to determine the effect of capital structure, company size, profitability, and institutional ownership on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. This study consisted of 65 samples of manufacturing companies that were selected using the purposive sampling method. The data used are secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). Data processing in this study was using Eviews 10 and Microsoft Excel 2007. The results of this study indicate that capital structure has a significant and positive influence on firm value, company size has a significant and negative influence on firm value, while profitability and institutional ownership have insignificant and negative influence on firm value. Simultaneously, capital structure, company size, profitability, and institutional ownership have a significant effect on firm value.